State border fences as a threat to habitat connectivity : a case study from South-Eastern Europe = Ograde na državnim granicama kao prijetnja povezanosti staništa : studija slučaja iz Jugoistočne Europe - Safner, Toni (Array, 2021)
The conservation value of transboundary management of wildlife populations in Europe, that marked end of the 20th and the beginning of the 21th century, has come under huge pressure since 2015 especially in the South-eastern Europe due to border fences construction in response to large influxes of refugees/migrants. The primary aim of this study was to present data on the direct impacts of the long fence on wildlife (e.g. fence-related mortality) across the Hungary–Croatia border. We collected data on fence-related animal mortality along 136 km of the fence in the first 28 months after its construction. In total, 64 ungulates (38 red deer, 23 roe deer, and three wild boar) were found entangled in or deceased due to the razor wire fence. In addition, we present direct (photographic) evidence of newly recorded behaviour of red deer, as they gather in huge herds attempting to cross the border fence between Hungary and Croatia. Short term effect of the border fence is reflected in direct animal mortality, and as obstruction to the movement and behaviour of animals. In the case that current fences will remain or continue to expand along the northern boundary of South-eastern Europe, it is likely that fragmented wildlife populations in the region will suffer from negative effects of genetic subdivision such as loss of alleles and reduced heterozygosity that can cause important long-term damage to their vitality.